Assessment of Philippine Integrated Management of Acute Malnutrition (PIMAM) Program Implementation and Challenges in Maguindanao Hospitals, Philippines - Saed Abdulrahman; Saidamin Bagolong (Philippine Association of Institutions for Research, Inc., 2023)
This study aimed to evaluate the implementation of the Philippine Integrated Management of Acute Malnutrition (PIMAM) Program in Maguindanao Provincial Hospital (MPH), Dinaig Municipal Hospital (DMH), and South Upi Municipal Hospital (SUMH), Philippines. Employing a descriptive-evaluative design, data were gathered from 107 respondents comprising top management and hospital staff, selected via purposive sampling. A survey questionnaire was utilized as the primary data collection tool, supplemented by secondary data obtained from hospitals' PIMAM-ITP coordinators regarding the status of patients upon discharge from the Inpatient Therapeutic Program (ITP). Data were analyzed using mean and percentage. Results indicated high levels of implementation of PIMAM-ITP across the hospitals concerning guidelines, facilities, materials, screening, treatment, and discharge procedures. Notably, 74% of discharged patients from ITP hospitals were classified as "successfully treated," with the remaining categorized as defaulter (16%), deceased (8%), medically transferred (2%), or non-respondent (0%). The program demonstrated effectiveness in systematically addressing acute malnutrition. However, challenges persisted, particularly concerning caregiver compliance and funding allocation for training on the National Guidelines for the Management of Severe Acute Malnutrition among personnel involved in program implementation.